Strategi Pemasaran Jasa Pendidikan dalam Meningkatkan Loyalitas Pelanggan - Nurdiana (Journal of Economic Education and Entrepreneurship Studies, 2022)
In the world of education, competition is increasingly unavoidable, even some educational institutions have lost their customers. Conditions of increasingly fierce competition continue to spur in order to exist and survive in carrying out the development of educational services. Some people must be able to understand the concept of marketing education services clearly so that educational services can be maintained. This is in accordance with the concept of loyalty which has an important role to complete the process of doing marketing to gain market share. The purpose of this study is to determine the types of educational services offered, the strategies used in marketing educational services, the obstacles experienced when doing marketing and to determine the response of consumers who use educational services.